# algebra II-URGENT

43,917 results, page 33

### algebra

(3/4x-1/6)(3/4x+1/6)

### Algebra

31 - 2/3X > 27, then X < ?

-42/2

x/8+1/6=-1/10

5a/2x + 7/10

f(x)=x+19

x+y=38; x-y=26-x

8-t/2=53

### Algebra

(4/x-2)-(7/x^2-4)=1

### Algebra 2

(3x^4-5x^3+7)/(x+1)

### algebra

x-3y+z=8 3x+y-2y=4 x-3y+2z=6

1/z+8/1/z-2

### Algebra

y-3y-7/7/20/14+5/2y

### Algebra

7/w+2/+(-8w-2)/w^2+2w

### Algebra

(7/w+2)+(-8w-2/w^2+2w)-(6-w/w)

3/5g+4=6 1/3

9X+y=2 -4X-y=17

b/3 + 6=82

x2 - 5x + 5 = 0

(8-i)^2(8+i)^2

(8-i)^2(8+i)^2

4^2+6^2=c^2

9n^2-1=0

Y=3X^2+9X-1

x2 - 5x + 5 = 0

### Algebra

-4x+1-2(x-1)= -4(x-4)

### algebra

x+2y=9(1) x=8-2y(2)

### Algebra 1

3x + 4y = -2 and 2x - 3y = 10

55/18=17/16+1/2x

### algebra

(1/t)(1/t)1/t)= -2

2x+y=4 -x+y=1

### algebra

If f(x)= x^2-2, then f(x+h)=?

### algebra 1

4/x-5 + 2/(x-5)^2

w/7 - 7/w = 0

y²-36/6-y

z-4/z+7 = 1/5

x²+6x-4y+1=0

ã2(9ã3 - 9ã9)

h(x)=4x-4

f(x)=2/5 x+3

-5/8- 3/4=

9d+3d-1d=14

### Algebra

(1/2a + 3/4b - 1/3c)^2

### algebra

-4 (9r+3) +5(3r+7)=

### algebra

a – 6 = 2b a + b = 15

### algebra

if 2k - 4 = 8, then k is what

30% of 59

x2+7x+10/x-9

Z-12 / 3=4

a+7b=17, a+2b=2

-2(t-7)-(t+8)=8

### algebra

m<-2 A)-1 9/10 B)0 C)-2 1/3

t-9(t+11)

### algebra

(x^3+2x+4x)/(x^3+8)

3(5y-5x)=45

x+1/3=5/6

### algebra 2

a when a,=-10 and d=3

### Algebra

Help . ? 1. 5/a-5 -1 = a/a-5 2. 65-n/n = 4+ 5/n 3. a/a-2+ 2/3 = 2/a-2 4. x-1/3+ x+2/4 = 1/6

-5x-10= 2-(x+4)

4x+(-9+3x)=-5

### algebra 1

What is 1/13 of 42?

### algebra 1

What is 40% of 84%?

3x/y - 5

(-2y) (-y+11)

3x+4x

### algebra

1/7x-x=-1/7(2x+84)

### Algebra 1

15 4/4 - 1 2/2 - 1 2/2 - 4 3/3?

### Algebra 1

|(3x+2)/2|=|(2x-3)/3|

what is 1=2n

### Algebra

x^3 + 6x^2 + 5x + 30 = 0

(x + 8)2 = 32

4=2/9(4y-2)

8w-8-6w=4w-7

### algebra

5/8m-3/8=1/2m=7/8

10^4/5^2

X+12=2x+6

### Algebra..

Help? If f = (1, 2), (2, 3), (3, 4), (4, 5), g = (1, -2), (3, -3), (5, -5), and h = (1, 0), (2, 1), (3, 2), 1. f+g 2. f-g 3. f*g

-2/5+6

x-3x^(1/2)+2=0

### Algebra 2

6X^(2/3)-5X^(1/3)-6=0

### Algebra 2

6X^(2/3)-5X^(1/3)-6=0

x-3x^1/2+2=0

3n^4-4n^2=-1

x-1/4=x/3+7 3/4

7 5/8+2/3+

3x-6=15

### Algebra 2

1. [3x^(5/2)]-9=0 2. [(x^2+9x+22)]^(3/2)=8 3. [(2x+3)]^(1/2)=4 4. [(5x-5)]^(2/3)=16

### Algebra

(2x+3)^(1/2)=4 (5x-5)^(2/3)=16

6x+7=25;3

5h+2(11-h)= -5

### Algebra 2

5/(2y+6)+1/(y-2)=3/(y+3)?

21/2m=11/5

4s=-28

### Algebra 2

1. |x^2-3x+3|=3 2. |x^2+2x+1|=-4 3. |3x+2|+3=0

5x/9-11=-51

N/5-9=1/5

### Algebra 2

[(x^2+4x+3)/(2x^2-x-10)]*[(2x^2+4x^3)/(x^2+3x)]*[(x)/(x^2+3x+2)]

(9-4n)(-4)

### Algebra 2

[(x^2+2x-15)/(x^2-4x-45)] / [(x^2+x-12)/(x^2-5x-36)]

(-36)/(-2) =